KOH developing solution composition for integrated circuit

通过在显影液中加入电子级氢氧化钾、显影增强剂和腰果酚席夫碱表面活性剂,解决了现有显影液在光刻工艺中显影不良、腐蚀金属和泡沫多的问题,实现了显影液的高效、环保和高品质的显影效果。

CN119439656APending Publication Date: 2025-02-14FUJIAN YOUDA ENVIRONMENTAL PROTECTION MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411856537.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing developer has problems such as poor development, corrosion of metal aluminum substrates, and more foams in the lithography process, resulting in low product yield and environmental pollution.

Method used

A KOH developing solution composition for integrated circuits is adopted, which contains 1-10% inorganic alkali (electronic grade potassium hydroxide), 1-5% development enhancer, and 0.5-10% cashew phenol Schiff base surfactivity The agent and high-purity water, through the synergistic effect of these components, improve the dispersion, wetting and stability of the developer.

Benefits of technology

The excellent development performance of the developer is achieved, good wettability, few metal impurities, small foam, no corrosion to the metal aluminum substrate, easy to rinse, no residue on the chip, and no pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119439656A_ABST
    Figure CN119439656A_ABST
Patent Text Reader

Abstract

The invention discloses a KOH developing solution composition for an integrated circuit. The composition is prepared from inorganic alkali, a developing enhancer, a cardanol Schiff base surfactant and high-purity water. The developing solution has the characteristics of excellent developing performance, good wettability, few metal impurities, small foam, no corrosion to a metal aluminum substrate, easiness in rinsing, no residue on a chip, no pollution to the environment and the like, and can meet the use performance and cleanliness requirements of a chip integrated circuit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wet electronic chemicals, and in particular relates to a KOH developer composition for integrated circuits. Background Art

[0002] The photolithography process is to form the designed circuit pattern on the surface of the wafer. It is one of the most important processes in the semiconductor process and one of the bottlenecks that currently limit the level of semiconductor manufacturing in my country. The photolithography process usually consists of two steps: first, the properties and structure of the photoresist itself are changed through exposure and development, so that the circuit pattern is formed on the photoresist layer and the circuit pattern is transferred; then, etching or deposition is carried out on the part of the wafer surface not covered by the photoresist to complete the manufacture of the circuit pattern.

[0003] With the rapid development of microelectronics technology, the line width and fineness of large-scale integrated circuits are gradually increasing, and the requirements for wet electronic chemicals are getting higher and higher. Semiconductor integrated circuit manufacturing requires wet electronic chemicals to reach SEMI G4 or above, especially the high-precision graphic process (photolithography process) is extremely difficult. The photolithography process has developed from G-line, I-line, KrF to the most advanced ArF and EUV today, and its progress is inseparable from the continuous development of photoresists and supporting developer reagents. Developers are in great demand in the field of wet electronic chemicals for integrated circuits. With the requirements for high-end integrated circuits, the use of high-performance developers is even more important.

[0004] Ultra-large-scale and ultra-large-scale chip integrated circuits all use 8-inch or 12-inch wafers. The developer needs to be evenly distributed on the surface of the photoresist. In most development processes, the developer (mostly tetramethylammonium hydroxide as the main reactant and ultrapure water as the solvent) is immersed or sprayed in contact with the exposed photoresist surface (mostly organic polymer materials). Due to the difference in material properties, there is a certain surface interfacial tension between the two, which is prone to poor development due to uneven contact. At the same time, because the development of the photoresist must be completed on the substrate, the developer will contact the substrate, but the main components of most developers on the market currently contain a large amount of organic alkali, which has problems such as corrosion of the metal aluminum substrate, poor development, and more foam, resulting in low product yield. In addition, in the application field of photoresist development, a large amount of foaming will weaken the wettability of the developer to the photoresist, resulting in the formation of microstructures on the surface of the exposed photoresist, resulting in weak or no development.

[0005] Patent CN 117761977A discloses an anti-corrosion alkaline developer, which is composed of 1-10wt% quaternary ammonium hydroxide, 0.1-5wt% metasilicate, 0.1-6wt% inorganic acid and / or organic acid, 0-1wt% surfactant and water. The developer has good corrosion inhibition and can accurately form patterns without corroding metals. However, the addition of organic silicon surfactants and defoamers can easily lead to silicon residues and poor development performance, while increasing industrial production costs. The defoamer itself has poor biodegradability and is not environmentally friendly. Patent CN 107121898A discloses a TFT-LCD display developer, which is composed of 22-26 parts of alkaline compounds, 7-14 parts of nonionic surfactants, 9-15 parts of penetrants and 42-54 parts of deionized water. The developer does not need to add a defoamer and has the characteristics of good development performance, no residue, a wide operating temperature range, less environmental pollution, etc. However, the addition of a large amount of organic bases can lead to corrosion of the metal aluminum substrate. Summary of the invention

[0006] In order to solve the above-mentioned problems, the present invention provides a KOH developer composition for integrated circuits, which has excellent developing performance, good wettability, less metal impurities, less foam, no corrosion to the metal aluminum substrate, easy rinsing, no residue on the chip, and no pollution to the environment.

[0007] To achieve the above object, the present invention adopts the following technical solutions: A KOH developer composition for integrated circuits, wherein the mass percentages of the components contained therein are as follows, based on the sum of the mass percentages being 100%: Inorganic alkali 1-10%, Development enhancer 1-5%, Surfactant 0.5-10%, Remaining amount of water.

[0008] Furthermore, the inorganic base is an electronic grade potassium hydroxide aqueous solution with a concentration of 45 wt %, and the metal impurity content thereof is less than 10 ppm.

[0009] Furthermore, the development enhancer is one or more of potassium metasilicate, sodium metasilicate, boric acid, potassium tetraborate, sodium tetraborate, phosphoric acid, citric acid, and pyromellitic acid.

[0010] Furthermore, the water is high-purity water with a resistivity of not less than 18 MΩ·cm.

[0011] Furthermore, the surfactant is a cardanol Schiff base surfactant, and its chemical structural formula is: , where R = C 15 H 31-2n, n is an integer between 0 and 3, preferably n=3.

[0012] The design of this surfactant has the following advantages: the carboxylic acid group can improve the solubility of the entire system in water, and it has good thermal stability, low toxicity, good water solubility, and is very environmentally friendly; cardanol sulfonate has excellent foam stability, its carbon chain is long, and the film has strong rigidity, which makes the foam easy to break and has a good foam suppression effect; Schiff base is an electron-donating organic corrosion inhibitor, which contains polar atoms with large electronegativity and lone pairs of electrons, and can fill lone pairs of electrons into the empty d orbitals of metal surface atoms to form coordination bonds, thereby forming chemical adsorption on the aluminum surface. At the same time, various active groups in the molecule can form physical adsorption on the aluminum surface through hydrogen bonds, etc., and a relatively stable corrosion inhibition film can be formed under the synergistic effect of the two adsorptions.

[0013] Furthermore, the preparation method of the surfactant comprises the following steps: (1) Synthesis of intermediate Ⅰ 0.03 mol of cardanol was dissolved in 50 mL of dichloromethane, and 12 g of chlorosulfonic acid was slowly added thereto at 0°C using a dropping funnel; after the addition was completed, the temperature was raised to 25°C and the reaction was carried out at a constant temperature for 3 hours; the reaction mixture was dissolved in 50 mL of anhydrous ethanol, and then 5 mol / L of sodium hydroxide solution was added to neutralize the reaction system until the pH value was 7, and the reaction was carried out at a constant temperature of 25°C for 3 hours, and the inorganic salt was removed by negative pressure filtration, and the reaction solvent in the system was removed by reduced pressure distillation of the filtrate at 40°C to obtain intermediate I; (2) Synthesis of intermediate II 0.05 mol of dodecanoyl chloride was added dropwise to 150 ml of toluene solution containing 0.2 mol of intermediate I, and the mixture was reacted at 70-80°C for 4 hours, and then cooled. Unreacted raw materials were washed out with an aqueous solution containing 0.15 mol of sodium hydroxide, and the solvent was removed by distillation, and then recrystallized with ethanol to obtain intermediate II. (3) Synthesis of intermediate III Take 0.1 mol of intermediate II and dissolve it in 80 ml of carbon disulfide, and add 0.1 mol of AlCl3. After reflux at 45 °C for 1 hour, evaporate the solvent, heat up to 120 °C and continue to react for 2 hours, then add an aqueous solution containing 0.1 mol of hydrochloric acid to hydrolyze the aluminum salt, extract with dichloromethane, add an aqueous solution containing 0.15 mol of sodium hydroxide to the extract under ice-water cooling and continuous stirring, filter and separate after solid is formed, add hydrochloric acid to acidify to pH 3-5, extract with dichloromethane, evaporate the solvent from the extract and recrystallize with ethanol to obtain intermediate III; (4) Synthesis of surfactants Take 0.05 mol of intermediate III and dissolve it in 100 ml of anhydrous ethanol by ultrasonic. Take 0.04 mol of p-aminobenzoic acid and dissolve it in 50 ml of anhydrous ethanol. Mix the two solutions, reflux them under magnetic stirring in a water bath at 85 °C for 3 h, and then let them stand overnight. After all the precipitates are precipitated, vacuum filter them, wash them with anhydrous ethanol for 2 to 3 times, drain them, and dry them in a vacuum drying oven at 40 °C to obtain the surfactant.

[0014] The invention solves the problem that the impurities remain on the film due to the large amount of metal impurities in the drug solution, which affects the connection between metal bonds, thereby causing poor gold eutectic properties and easy detachment of gold balls from the electrode; the invention avoids the problems of uneven development, failure to disperse the photoresist, slow development speed, and line width not meeting the requirements in the development process due to the film thickness by adding a development enhancer; and improves the dispersibility, wettability, and solubility of the developer composition by adding a cardanol Schiff base surfactant, thereby slowing down the corrosion rate of metal aluminum.

[0015] The beneficial effects of the present invention are: (1) The present invention reduces the content of metal impurity ions in the developer, helps to improve the residual contamination caused by the metal impurity ions in the developer, and solves the problem of low residual gold value.

[0016] (2) The present invention adds a cardanol Schiff base surfactant to the developer system. The cardanol Schiff base surfactant is a hydrophobic chain surfactant with a double hydrophilic group, which has good solubility in water, good rinsing performance, and good dispersibility. The cardanol Schiff base surfactant contains both a hydrophilic group and a hydrophobic group, and has a certain surface activity, so that the surface tension of the entire developer system can be significantly reduced when the surfactant is used in a small amount, thereby overcoming the deficiency that the tetramethylammonium hydroxide developer has too large a surface tension and cannot fully infiltrate the photoresist, and also avoids the generation of foam due to excessive surfactant, thereby slowing down the production progress of the developer, improving the development performance, and avoiding the interference of the presence of foam on the reaction between the reactive group and the dilute alkaline solution, thereby preventing the incomplete dissolution of the residue in the unexposed part.

[0017] (3) The various components in the KOH developer composition for integrated circuits of the present invention cooperate with each other to play a synergistic role. It has the characteristics of excellent developing performance, good wettability, less metal impurities, less foam, no corrosion to the metal aluminum substrate, easy rinsing, no residue on the chip, and no pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The figure is a synthesis process diagram of the cardanol Schiff base surfactant used in the present invention. DETAILED DESCRIPTION

[0019] A KOH developer composition for integrated circuits, wherein the sum of the mass percentages is 100%, the components contained therein and the mass percentages of the components are as follows: Inorganic alkali 1-10%, Development enhancer 1-5%, Surfactant 0.5-10%, Remaining amount of water.

[0020] Wherein, the inorganic base is an electronic grade potassium hydroxide aqueous solution with a concentration of 45wt%, and its metal impurity content is less than 10ppm.

[0021] The development enhancer is one or more of potassium metasilicate, sodium metasilicate, boric acid, potassium tetraborate, sodium tetraborate, phosphoric acid, citric acid, and pyromellitic acid.

[0022] The surfactant is a cardanol Schiff base surfactant, and its chemical structural formula is: , where R = C 15 H 31-2n , n is an integer between 0 and 3.

[0023] The water is high-purity water with a resistivity of not less than 18 MΩ·cm.

[0024] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0025] The cardanol Schiff base surfactant used in the embodiment has n=3, and its chemical structural formula is: ; The preparation method comprises the following steps: (1) Synthesis of intermediate Ⅰ 0.03 mol of cardanol was dissolved in 50 mL of dichloromethane, and 12 g of chlorosulfonic acid was slowly added thereto at 0°C using a dropping funnel; after the addition was completed, the temperature was raised to 25°C and the reaction was carried out at a constant temperature for 3 hours; the reaction mixture was dissolved in 50 mL of anhydrous ethanol, and then 5 mol / L of sodium hydroxide solution was added to neutralize the reaction system until the pH value was 7, and the reaction was carried out at a constant temperature of 25°C for 3 hours, and the inorganic salt was removed by negative pressure filtration, and the reaction solvent in the system was removed by reduced pressure distillation of the filtrate at 40°C to obtain intermediate I; (2) Synthesis of intermediate II 0.05 mol of dodecanoyl chloride was added dropwise to 150 ml of toluene solution containing 0.2 mol of intermediate I, and the mixture was reacted at 70-80°C for 4 hours, and then cooled. Unreacted raw materials were washed out with an aqueous solution containing 0.15 mol of sodium hydroxide, and the solvent was removed by distillation, and then recrystallized with ethanol to obtain intermediate II. (3) Synthesis of intermediate III Take 0.1 mol of intermediate II and dissolve it in 80 ml of carbon disulfide, and add 0.1 mol of AlCl3. After reflux at 45 °C for 1 hour, evaporate the solvent, heat up to 120 °C and continue to react for 2 hours, then add an aqueous solution containing 0.1 mol of hydrochloric acid to hydrolyze the aluminum salt, extract with dichloromethane, add an aqueous solution containing 0.15 mol of sodium hydroxide to the extract under ice-water cooling and continuous stirring, filter and separate after solid is formed, add hydrochloric acid to acidify to pH 3-5, extract with dichloromethane, evaporate the solvent from the extract and recrystallize with ethanol to obtain intermediate III; (4) Synthesis of surfactants Take 0.05 mol of intermediate III and dissolve it in 100 ml of anhydrous ethanol by ultrasonic. Take 0.04 mol of p-aminobenzoic acid and dissolve it in 50 ml of anhydrous ethanol. After mixing the above two solutions, transfer them into a 250 ml round-bottom flask, reflux them under magnetic stirring in a water bath at 85 °C for 3 h, then let them stand overnight, and after all the precipitates are precipitated, vacuum filter them, wash them with anhydrous ethanol for 2 to 3 times, drain them, and dry them in a vacuum drying oven at 40 °C to obtain the target product.

[0026] Its characterization data are as follows: 1 H NMR (300 MHz, DMSO- d6 ), d :0.88 (t,3H,CH3), 1.26 (m,10H,CH2), 1.30 (m,4H,CH2), 1.33 (m,2H,CH2), 1.54 (m,2H,CH2), 2.11 (t,2H,CH2), 7.43 (d,2H,ArH), 8.18 (d,2H,ArH), 12.71 (s,1H,OH),7.50 (s,1H,ArH),7.17 (s,1H,ArH),9.4 5 (s,1H,OH), 2.63 (t,2H,CH2), 1.59 (m,2H,CH2), 1.29 (m,4H,CH2), 2.16 (m,2H,CH2), 5.43 (m,4H,CH), 2.00 (m,8H,CH2), 4.88-5.82 (m,3H,CH=CH2).

[0027] 13 C NMR (125 MHz, DMSO- d6 ), d:14.1,22.7,31.9,29.3,29.6,29.7,23.7,31.3,164.6,130.2,136.4,139.2,117.4,160.3,113.4,156.5,122.2,131.6,128.7,169.3,32.0,31.0,30.7,29.9,33.7,131.3,129.8,33.2,130.5,32.9,33.9,137.0,116.4.

[0028] HRMS calculated value C 26 H 54 N4O8(M+H) + :701.37, measured value 701.94. Example

[0029] According to the formula in Table 1, developer compositions of different compositions were prepared.

[0030] Table 1 Components and their contents in different developer compositions

[0031] The developer compositions prepared in the examples and comparative examples were tested for the following performance parameters, and the results are shown in Table 2: 1. Test of metal impurity content in liquid medicine The metal impurities in the solution are tested by inductively coupled plasma (ICP-MS / OES); (ii) Foam test Take 30ml of the drug solution (25℃) in a 100ml measuring cylinder, shake it up and down 20 times, and record the foam volume (ml); (III) Development performance test 1) Developer temperature: 23°C, 2) Development time after the first spraying: 82s, 3) Spraying developer after resting: 11s, 4) Development time after the second spraying: 76s, 5) After development, rinse with high-purity water, blow dry with nitrogen, and observe under a microscope: ① Whether the developed pattern is clear; ②Whether there is any photoresist residue; ③Whether the substrate is corroded; Table 2 Performance parameters of different developer compositions

[0032] It can be seen from Table 2 that the developer composition prepared in the example has the characteristics of excellent developing performance, good wettability, less metal impurities, less foam, no corrosion to the metal aluminum substrate, easy rinsing, and no residue on the chip.

[0033] Compared with Example 1, in Comparative Example 1, industrial-grade potassium hydroxide is added. Under the operating conditions, the developed pattern is clear and there is no corrosion to the substrate. However, due to the large amount of metal impurities in the liquid medicine, metal residues are left after development; in Comparative Example 2, an organic base is added. The pattern is unclear after development and there is corrosion to the substrate; in Comparative Example 3, a development enhancer is not included and the pattern is unclear after development; in Comparative Example 4, polyoxyethylene sorbitan monooleate is used as the surfactant. Under the operating conditions, the pattern is unclear after development, there is slight photoresist residue and there is slight corrosion to the substrate; in Comparative Example 5, no surfactant is included. The pattern is unclear after development, the photoresist residue is serious and there is serious corrosion to the substrate; in Comparative Example 6, a cardanol sulfonate surfactant is used. The developing performance meets the requirements, but there is slight corrosion to the substrate; in Comparative Example 7, a para-aminobenzoic acid Schiff base surfactant is used. There is no corrosion to the substrate, but its development is poor (weak or no development) due to its rich foam.

[0034] It can be seen that the components of the KOH developer composition for integrated circuits of the present invention cooperate with each other to play a synergistic role, and each component is indispensable. The developer composed of the KOH developer has the characteristics of excellent developing performance, good wettability, less metal impurities, less foam, no corrosion to the metal aluminum substrate, easy rinsing, no residue on the chip, no pollution to the environment, etc.

[0035] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A KOH developer composition for integrated circuits, characterized in that: When the sum of the mass percentages is 100%, the mass percentages of the components in the KOH developer composition are as follows: Inorganic alkali 1-10%, Development enhancer 1-5%, Surfactant 0.5-10%, Remaining amount of water.

2. The KOH developer composition for integrated circuits according to claim 1, characterized in that: The inorganic base is an electronic grade potassium hydroxide aqueous solution with a concentration of 45 wt %, and the metal impurity content thereof is less than 10 ppm.

3. The KOH developer composition for integrated circuits according to claim 1, characterized in that: The development enhancer is one or more of potassium metasilicate, sodium metasilicate, boric acid, potassium tetraborate, sodium tetraborate, phosphoric acid, citric acid, and pyromellitic acid.

4. The KOH developer composition for integrated circuits according to claim 1, characterized in that: The surfactant is a cardanol Schiff base surfactant, and its chemical structural formula is: , where R = C 15 H 31-2n , n is an integer between 0 and 3.

5. The KOH developer composition for integrated circuits according to claim 4, characterized in that: The preparation method of the surfactant comprises the following steps: (1) Synthesis of intermediate Ⅰ 0.03 mol of cardanol was dissolved in 50 mL of dichloromethane, and 12 g of chlorosulfonic acid was slowly added thereto at 0°C using a dropping funnel; after the addition was completed, the temperature was raised to 25°C and the reaction was carried out at a constant temperature for 3 hours; the reaction mixture was dissolved in 50 mL of anhydrous ethanol, and then 5 mol / L of sodium hydroxide solution was added to neutralize the reaction system until the pH value was 7, and the reaction was carried out at a constant temperature of 25°C for 3 hours, and the inorganic salt was removed by negative pressure filtration, and the reaction solvent in the system was removed by reduced pressure distillation of the filtrate at 40°C to obtain intermediate I; (2) Synthesis of intermediate II 0.05 mol of dodecanoyl chloride was added dropwise to 150 ml of toluene solution containing 0.2 mol of intermediate I, and the mixture was reacted at 70-80°C for 4 hours, and then cooled. Unreacted raw materials were washed out with an aqueous solution containing 0.15 mol of sodium hydroxide, and the solvent was removed by distillation, and then recrystallized with ethanol to obtain intermediate II. (3) Synthesis of intermediate III Take 0.1 mol of intermediate II and dissolve it in 80 ml of carbon disulfide, and add 0.1 mol of AlCl3. After reflux at 45 °C for 1 hour, evaporate the solvent, heat up to 120 °C and continue to react for 2 hours, then add an aqueous solution containing 0.1 mol of hydrochloric acid to hydrolyze the aluminum salt, extract with dichloromethane, add an aqueous solution containing 0.15 mol of sodium hydroxide to the extract under ice-water cooling and continuous stirring, filter and separate after solid is formed, add hydrochloric acid to acidify to pH 3-5, extract with dichloromethane, evaporate the solvent from the extract and recrystallize with ethanol to obtain intermediate III; (4) Synthesis of surfactants Take 0.05 mol of intermediate III and dissolve it in 100 ml of anhydrous ethanol by ultrasonication; take 0.04 mol of p-aminobenzoic acid and dissolve it in 50 ml of anhydrous ethanol; mix the above two solutions, stir under magnetic reflux in a water bath at 85 °C for 3 h, and then let it stand overnight until all the precipitation is After precipitation, vacuum filtration is performed, and the product is washed 2-3 times with anhydrous ethanol, dried, and placed in a vacuum drying oven at 40°C to obtain the surfactant.

6. The KOH developer composition for integrated circuits according to claim 1, characterized in that: The water is high-purity water with a resistivity of not less than 18 MΩ·cm.

Citation Information

Patent Citations

  • Development liquid for TFT-LCD (thin film transistor-liquid crystal display) displaying

    CN107121898A